Simultaneous viral whole-genome sequencing and differential expression profiling in respiratory syncytial virus infection of infants - Lin, G-L; Golubchik, T; Drysdale, S; O'Connor, D; Jefferies, K; Brown, A; de Cesare, M; Bonsall, D; Ansari, MA; Aerssens, J; Bont, L; Openshaw, P; et al. (Oxford University Press, 2020)
Targeted metagenomics using strand-specific libraries with target enrichment is a sensitive, generalized approach to pathogen sequencing and transcriptome profiling. Using this method, we recovered 13 (76%) complete human respiratory syncytial virus (RSV) genomes from 17 clinical respiratory samples, reconstructed the phylogeny of the infecting viruses, and detected differential gene expression between two RSV subgroups, specifically, a lower expression of the P gene and a higher expression of the M2 gene in RSV-A than in RSV-B. This methodology can help to relate viral genetics to clinical phenotype and facilitate ongoing population-level RSV surveillance and vaccine development.